Modern Trends in Medicinal Chemistry: Techniques, Applications, and Innovations (VOLUME-1) - Sahu, Subash Chandra; Behera, Chandini (AG Volumes, 2025)
Modern Trends in Medicinal Chemistry: Techniques, Applications, and Innovations (Volume-1) is a timely and comprehensive compilation of peer-reviewed chapters that collectively reflect the evolving landscape of modern medicinal chemistry. With the convergence of traditional synthetic methods and emerging interdisciplinary technologies, this book provides a scholarly platform for understanding the significant innovations shaping the pharmaceutical sciences today. This volume features twelve well-researched chapters authored by reputed academicians and scientists. The topics span across advanced drug design, green chemistry applications, natural product-based drug discovery, targeted drug delivery systems, nanotechnology in medicine, and the application of artificial intelligence and computational tools in drug development. Each contribution provides critical insights into the challenges and future directions within its thematic focus, while offering practical perspectives for academic research, clinical translation, and industry relevance. Designed for postgraduate students, researchers, educators, and professionals in the pharmaceutical and biomedical sectors, this book bridges theoretical frameworks and applied science. It encourages interdisciplinary thinking and highlights global research efforts aimed at enhancing therapeutic outcomes and achieving innovation-driven healthcare solutions. As the first volume of an ongoing series, this book lays a strong foundation for subsequent explorations in the field of medicinal chemistry.